EXAMINATION OF FINGERNAIL CONTENTS FOR THE PRESENCE OF OVA/CYSTS OF INTESTINAL PARASITES FROM PUPILS ATTENDING PLATEAU STATE POLYTECHNIC BARKIN LADI HEIPANG CAMPUS STAFF PRIMARY SCHOOL - Dasat Shwamyil, George; Olusola, Kum Folakemi; Garba, Maryam (FUDMA Journal of Sciences, 2026)
Intestinal parasitic infections among primary school-age children in developing countries, including Nigeria, are an escalating public health issue. These parasites, often transmitted via the oral-faecal route, are a leading cause of diarrhoea. This study focused on examining the fingernail contents of students at Plateau State Polytechnic (PSP) Staff School in Heipang, Barkin Ladi, Plateau State, Nigeria. A total of 100 fingernail samples were analyzed microscopically for the presence of parasite ova/cysts. The investigation revealed that 71% of the pupils harboured at least one type of parasite cyst/ova, resulting in a 98.69% prevalence rate. The most commonly detected parasites were Schistosoma mansoni and Ancylostoma duodenale, each found in 17% of the samples. This was followed by Ascaris lumbricoides, detected in 14% of the cases. Gender analysis showed that 78% of male children tested positive for various parasite cysts/ova, while 64% of female pupils were affected. Age-related analysis indicated that children aged 11-15 had an 80% prevalence rate, those aged 1-5 had a 66.67% prevalence, and children aged 6-10 had a 64.30% prevalence rate. The presence of fingernail parasites in primary school children can lead to chronic infections, negatively impacting their health, nutrition, cognitive development, and educational success. Regular cleaning and trimming of fingernails, along with consistent hand hygiene practices, are essential measures to reduce the risk of parasitic transmission among primary school pupils.